THE EFFECTIVENESS OF THE MAMUJU COOL CARD POLICY IN IMPROVING COMMUNITY WELFARE IN MAMUJU REGENCY - Nur Ainung Sarmila; Haedar Akib; Didin Halim (Jurnal Aktor, 2026)
This study aims to describe the effectiveness of the Kartu Mamuju Keren policy in improving the welfare of the people in Mamuju Regency. This research is a descriptive qualitative study, with data collection techniques including observation, interviews, and documentation. The data were analyzed through stages of data condensation, data presentation, and drawing conclusions. The results of the study show that, in general, the Kartu Mamuju Keren program is effective in providing access to social and health services. However, the program still faces several challenges, such as a lack of transparency in the data collection and distribution processes, as well as unequal distribution of the program's benefits. Additionally, improvements are needed in terms of program socialization, system integration, and cooperation among all involved parties.